The Influence of International Trade on the Rupiah Exchange Rate - Rizsa Nabillah; Lesamana Rizki Samora; Muliana Putri Yohana Tobing; Khairani Alawiyah Matondang; Riza Indriani (PT FORMOSA CENDEKIA GLOBAL, 2023)
Fluctuations of exchange rate against in the Rupiah can be influenced by international trade which makes the Rupiah exchange rate depreciate or appreciate. The purpose of this study is to recognize the differences in the effect of international trade variables on the Rupiah exchange rate. The model considered for maintaining variables can connect the effects of international trade with the Rupiah exchange rate that occurred before using the Ordinary Least Square (OLS) method. OLS estimation shows that the independent variables, namely exports, imports, and interest rates have a significant influence on the expectations of the Rupiah exchange rate, while variable interest rates cannot significantly influence the Rupiah exchange rate. In conclusion, the export, import and interest rates policies are considered to affect the rupiah exchange rate if Indonesia does not change interest rates simultaneously and other macro policy variables.